Correlation between philosophy and theory of state and law - Grygor, Oleg; Krysiuk, Yuri; Boyko, Angela; Zubov, Vadim; Sinegub, Igor (My University, 2021)
At first glance, the relationship between philosophy and theory of law is not applied but is considered a purely theoretical aspect. This thesis is not correct due to the adoption of the European legal standard of human and civil rights, the role of philosophy of law, the foundations of the theory of state and law in the training of lawyers, the formation of future lawyers of high philosophical and methodological culture. In this article, based on the analysis of the history of philosophy of law and the general theory of state and law and their development, the authors justify as an autonomous status in the jurisprudence of the two disciplines, their relationship and vice versa - differences. To do this, the authors explored the historical excursion of world philosophical and legal thought, grouped scientific and theoretical views on the relationship between philosophy of law and theory of state and law and provided an argument for the close intersection of philosophy of law and theory of state and law, mobility between scientific disciplines. Close contact between philosophy and jurisprudence contributes to the understanding of law not only as a function of the state but also the essence of human spirituality. The authors concluded that the in-depth study of scientific and theoretical aspects of the relationship between philosophy, philosophy of law and theory of state and law is the result of bridging the gap between theory and practice and will further focus on expanding the interaction of philosophy, theory and law results of the functioning of the state and law. Emphasizing the relevance of the topic in terms of bridging the significant gap between theory and practice, between the declarative provisions of laws and their actual implementation, the legal, scientific community is increasingly expanding to enter the plane of the practical application of philosophical - theoretical thought.
Keywords: philosophy; philosophy of state and law; theory of state and law